TCAD simulation capabilities towards gate leakage current analysis of advanced AlGaN/GaN HEMT devices. (September 2017) - Mukherjee, K.; Darracq, F.; Curutchet, A.; Malbert, N.; Labat, N.
Abstract: 2D TCAD Sentaurus simulations based on Drift-Diffusion transport are performed to identify the modeling parameters that crucially affect the reliability characteristics of AlGaN/GaN HEMT devices, demonstrated by their effects on the gate leakage characteristic. The behavioural nature and impact of each parameter on the leakage performance is discussed. Schottky gate tunneling and trapping effects within the structure are two major reliability issues that modulate the leakage characteristic. Hence, their contributions are precisely modeled. A simulation methodology is presented to recognize the relative control of individual parameters on distinct regions of the leakage characteristic. This modeling approach is demonstrated for a GaN HEMT technology and can be further applied to facilitate reliability comparisons across different device technologies. This validates TCAD simulation to be an effective aiding tool in reviewing and interpreting GaN HEMT reliability performance and design choices. Highlights: 2D TCAD Drift-Diffusion simulations performed to identify impact on gate leakage Parameters crucially affecting reliability of GaN HEMTs are identified. A simulation methodology recognizes relative parameter control over IG -VG . Facilitates reliability and performance comparisons across device technologies